Pacemaker upgrade to Cardiac Resynchronization Therapy-defibrillator or Cardiac Resynchronization Therapy-pacemaker without prior ventricular arrhythmias. (19th May 2022) - Schwertner, W R; Tokodi, M; Behon, A; Veres, B; Merkel, E; Kuthi, L; Masszi, R; Kovacs, A; Zima, E; Geller, L; Osztheimer, I; Kosztin, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the ÚNKP-21-3-II-SE-47, ÚNKP-20-3-I-SE-43 New National Excellence Program if the Ministry for Innovation and Technology in Hungary. Project no. NVKP_16-1–2016-0017 ('National Heart Program') has been implemented with the support provided by the National Research, Development and Innovation Fund of Hungary, funded under the NVKP_16 funding scheme. The research was financed by the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging thematic programmes of the Semmelweis University. This work was also supported by the Semmelweis 250+ Excellence PhD Scholarship (EFOP-3.6.3-VEKOP-16-2017-00009). Background: Cardiac Resynchronization Therapy (CRT) can reverse the harmful effects of right ventricular pacing (RVP). Data are scarce on comparing long-term survival among patients who undergone CRT-defibrillator (CRT-D) or CRT-pacemaker (CRT-P) upgrade from pacemakers (PM) without prior ventricular arrhythmias (VAs). Purpose: We compared the differences in long-term all-cause mortality among PM patients receiving CRT-D or CRT-P upgrade. Methods: Patients with conventional PMs developing heart failure despite optimal medical treatment and a high rate of RVP with no prior VAs were included. Altogether 326 patients were investigated, 117 (36%) upgraded to CRT-D, 209 (64%) to CRT-P in our retrospective registry. The primary endpoint was all-cause mortality. Subgroup analyses were performed by comorbidities and CRT device types. Using topological data analysis, we identified risk groups based on the primary endpoint. Results: During the median follow-up time of 3.6 years, 33 (28%) CRT-D and 145 (69%) of CRT-P upgrade patients reached the primary endpoint. The CRT-D upgrade group showed a lower risk of all-cause mortality in the total cohort (HR: 0.55; 95% CI: 0.38-0.81; p=0.002) and by ischaemic aetiology (HR: 0.47; 95% CI: 0.29-0.76; p=0.002) compared to CRT-P. After adjustment, CRT-D, male gender and loop diuretics proved as independent predictors of all-cause mortality. Patients upgraded with CRT-D demonstrated favourable survival in the high-risk group over CRT-P. Conclusions: Patients had survival benefit after CRT-D upgrade, compared to CRT-P, in the high-risk group and with ischaemic heart failre aetiology. However, no difference could be observed between the two groups among low- and intermediate-risk patients.